Poems - Owen, Wilfred, 1893-1918; Sassoon, Siegfried, 1886-1967 (Salt Lake City, UT : Project Gutenberg, 1997)
"Poems by Wilfred Owen" is a collection of war poetry published posthumously in the early 20th century, encompassing the poignant and tragic themes surrounding World War I. Written mainly during Owen's time as a soldier, the poems delve deeply into the horrors of combat, the futility of war, and the emotional and physical scars it leaves on individuals and society. Owen's work stands out for its stark realism and empathetic portrayal of soldiers' experiences, making it a critical commentary on the glorification of war. The collection contains notable poems such as "Dulce et Decorum est," which contrasts the romanticism often associated with warfare with the brutal reality faced by soldiers, and "Anthem for Doomed Youth," which mourns the loss of life in battle while critiquing the lack of traditional mourning rituals for fallen soldiers. Owen's poems reflect both personal grief and broader societal themes, using vivid imagery and innovative language to capture the trauma and disillusionment of a generation. The collection ultimately serves as a powerful testament to the human cost of war, advocating for remembrance and compassion over heroism and glory. (This is an automatically generated summary.)
Preface -- Strange meeting -- Greater love -- Apologia pro Poemate Meo -- The show -- Mental cases -- Parable of the old men and the young -- Arms and the boy -- Anthem for doomed youth -- The send-off -- Insensibility -- Dulce et decorum est -- The sentry -- The dead-beat -- Exposure -- Spring offensive -- The chances -- S.I.W. -- Futility -- Smile, smile, smile -- Conscious -- A terre -- Wild with all regrets -- Disabled -- The end.
Release date is 1997-09-01
Produced by Alan R. Light, Gary M. Johnson, and David Widger
Keywords: World War, 1914-1918 -- Poetry; English poetry -- 20th century; War poetry